Semi-Purified Saponins of Holothuria poli Associated Antiproliferation in Tumor Cell Lines. (21st April 2022) - Mert-Ozupek, Nazli; Basbinar, Yasemin; Uysal-Kilic, Tugba; Koz, Omer; Ellidokuz, Hulya; Cavas, Levent
Abstract: The incidence of cancer has exhibited an increasing trend in recent years because of many reasons such as environmental and nutritional factors. There is a great need for the development of new and natural molecules with lower side effects in the therapy of cancer. It was aimed to evaluate the antiproliferative effect of semi-purified triterpene glycosides of Holothuria poli on different human cancer cell lines. The body walls of H. poli as the main sources of saponins were used and the saponin content of the extract was characterized by MALDI-TOF/MS. The antiproliferation activity of the characterized extract was tested on cancer cell lines. The extract showed antiproliferative effect on the studied cancer cell lines. The mass analysis results reveal that Holothurin A is one of the saponins within the extract. The measured IC50 values were found as 31.41 ± 2.20, 77.45 ± 0.23, and 34.79 ± 0.90 µg mL −1 for HT-29, UPCI-SCC-131, and T84 cell lines, respectively. H. poli secretes not only specific saponins but also a cocktail of them. Specific versus. cocktails of the saponins and by also applying organic modification must be studied in further research to understand their mechanisms in the antiproliferation studies since this paper reveals promising results.